سورۃ الرحمٰن میں "فَبِأَيِّ آلَاءِ رَبِّكُمَا تُكَذِّبَانِ" کے تکرار کے روحانی و نفسیاتی اثرات:ایک مطالعہ: The Spiritual and Psychological Effects of the Repeated Refrain “Then Which of the Favors of Your Lord Will You Both Deny?” in Surah Ar-Rahman: A Comparative Study (Al-Aasar, 2025)
Surah Ar-Rahman, often termed the “Bride of the Qur’an,” stands unique in the entire scripture for repeating a single rhetorical question 31 times: “Then which of the favors of your Lord will you both deny?” (فَبِأَيِّ آلَاءِ رَبِّكُمَا تُكَذِّبَان). This deliberate, rhythmic repetition is far more than a literary ornament; it functions as a profound spiritual, psychological, and neuro-cognitive intervention designed to awaken gratitude, rewire perception, and restore inner equilibrium.The present study explores the multi-layered effects of this refrain from spiritual, psychological, and contemporary neuroscientific perspectives. Spiritually, the repeated question serves as a gentle yet insistent call to remembrance (tadhkir), constantly redirecting human consciousness from complaint to gratitude, from forgetfulness to recognition of divine generosity, and from ingratitude to repentance. Psychologically, the refrain operates as a powerful cognitive reframing tool and emotional anchor, transforming negative mental states into positive ones by compelling the listener to consciously acknowledge blessings even amid hardship. Recent findings in positive psychology and heart-brain coherence research corroborate that sustained engagement with this repetition elevates serotonin and dopamine levels, significantly reduces symptoms of anxiety and depression, and induces measurable physiological states of calm and coherence.The refrain’s dual address (to both human beings and jinn) universalizes the message, while its placement after pairs of cosmic and personal favors creates a rhythmic alternation between contemplation and response, mirroring the natural pulse of remembrance and gratitude. The study concludes that the 31-fold repetition constitutes a built-in therapeutic protocol: a divinely engineered gratitude practice that predates and surpasses modern mindfulness and cognitive-behavioral interventions by linking temporal gratitude with eternal reward.Far from being repetitive in a redundant sense, “Then which of the favors of your Lord will you both deny?” functions as a transformative spiritual technology that continuously recalibrates the human heart toward permanent alignment with divine mercy, making Surah Ar-Rahman one of the most powerful antidotes to the spiritual and psychological maladies of the contemporary age.